A Han Chinese Family With Early-Onset Parkinson's Disease Carrying Novel Frameshift Mutation and Compound Heterozygous Mutation of PRKN Appearing Incompatible With MDS Clinical Diagnostic Criteria - Gao, Chenyu; Huang, Ting; Chen, Rui; Yuan, Zhenhua; Tian, Youyong; Zhang, Yingdong (Frontiers in Neurology, 2020)
Around 15% of patients with Parkinson’s disease (PD) have a family history, and 5–10% have confirmed genetic causes. PRKN is the most common gene responsible for early-onset Parkinson’s disease (EOPD), while rare variants of PLA2G6 likely raise PD susceptibility in the Chinese population. We investigated the genetic information of 13 members of a Han Chinese family with known EOPD by whole-exome sequencing and Sanger sequencing, and analyzed the clinical history, physical examination, blood laboratory test, and brain imaging data of the patients. Two members, including the proband, were suspected of having EOPD. A novel homozygous frameshift mutation, c.856delT, and a compound heterozygous mutation, c.1321T>C/ c.856delT of PRKN, were identified, as well as two single nucleotide variants of PLA2G6 and TENM4. The proband exhibited a rare symmetrical resting tremor limited to her lower limbs and never exhibited signs of rigidity. 18F-DOPA PET/CT scan indicated symmetrical reduced signaling in the striatum. The novel frameshift mutation and compound heterozygous mutation of PRKN are likely to be the genetic causes of EOPD in this family.